2021
DOI: 10.18632/aging.202774
|View full text |Cite|
|
Sign up to set email alerts
|

Suppressing the KIF20A/NUAK1/Nrf2/GPX4 signaling pathway induces ferroptosis and enhances the sensitivity of colorectal cancer to oxaliplatin

Abstract: Oxaliplatin resistance can develop in colorectal cancer (CRC), which may involve inhibition of ferroptosis, although further research is needed to understand this potential mechanism. We evaluated CRC cells with acquired oxaliplatin resistance (HCT116-Or) or congenital resistance (H716) to determine whether a ferroptosis inducer (RSL3) or inhibitor (liproxstatin-1) could modulate the effects of oxaliplatin. The results suggested that induction of ferroptosis could significantly reverse the oxaliplatin resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
56
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(56 citation statements)
references
References 40 publications
0
56
0
Order By: Relevance
“…Mechanistically, we demonstrated that Nrf2/HO-1 is essential for cetuximab to promote RSL3-induced ferroptosis in KRAS mutant CRC cells. Disruption of the Nrf2/HO-1 axis was previously shown to contribute to the promotion of ferroptosis [ 40 42 ]. In this study, we assessed the expression of Nrf2/HO-1 both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, we demonstrated that Nrf2/HO-1 is essential for cetuximab to promote RSL3-induced ferroptosis in KRAS mutant CRC cells. Disruption of the Nrf2/HO-1 axis was previously shown to contribute to the promotion of ferroptosis [ 40 42 ]. In this study, we assessed the expression of Nrf2/HO-1 both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor immunotherapy ( Wang et al, 2014 ; Ning et al, 2015 ), N6-methyladenosine (m6A) modification ( Bai et al, 2019 ; Yang et al, 2020 ), ferroptosis ( Ma et al, 2018 ; Yang et al, 2021 ), and competing endogenous RNA (ceRNA) network ( Zhao et al, 2021 ) are hot topics of cancer gene therapy, which are broadly utilized in the investigation and therapy of CRC. Nevertheless, there are few research studies on the comprehensive analysis of SLC2A1 in CRC, particularly the relation between SLC2A1 and immune therapy, m6A modification, ferroptosis, and ceRNA regulatory network of CRC.…”
Section: Introductionmentioning
confidence: 99%
“…However, less than 40% patients with advanced CRC could benefit from oxaliplatin due to the development of drug resistance ( Hsu et al, 2018 ). A recent study has shown that congenital or acquired oxaliplatin resistance in CRC cell lines could be reversed by the treatment of RSL3 (a ferroptosis inducer) ( Yang et al, 2021 ). Another broad-spectrum anti-cancer drug, vincristine (21.3 HS vs. 2.8 LS, μM/L, p < 0.05 ), also inevitably falls into the dilemma of drug resistance after a period of usage ( Xia et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%